تأثير جائحة كوفيد 19 على مردودية المؤسسات الصيدلانية - شهرزاد لبناوي; ريم ماضي (My University, 2021)
This study aimed to identify the respondents’ perceptions about the emerging corona virus - Covid 19 - among workers in pharmaceutical institutions in the state of Souk Ahras and the impact of this on the profitability of these institutions, and to achieve this formula a main hypothesis that includes two sub-hypotheses, the first is the composition of the study community from a number of pharmacies In the state, where we chose a simple random sample and the questionnaire was distributed to all of them through several field visits and 19 valid questionnaires were retrieved for statistical analysis, and several statistical methods were relied on in analyzing the data, including descriptive statistics measures, standard deviation analysis ... Where the study reached several results, most notably, the presence of a significant moral role of the emerging corona virus on the strata of society and also its great impact on the profitability and activity of pharmaceutical institutions . And the study concluded to a number of recommendations, the most important of which are: The employees of pharmaceutical institutions should provide adequate support to the citizen in order to confront the disease and confront it, and to ensure that infection does not spread between individuals. They also work to provide advice and instructions necessary for prevention and how to use medicines. ............................................................. هدفت هذه الدراسة الى التعرف على تصورات المبحوثين حول فيروس كورونا المستجد كوفيد 11 لدى العاملين بالمؤسسات – - الصيدلانية بولاية سوق أهراس و أثر ذلك على مردودية هذه المؤسسات، و لتحقيق ذلك صيغت فرضية رئيسية متضمنة فرضيتين فرعيتين الاولى تتمثل في تكوين مجتمع الدراسة من عدد من الصيدليات في الولاية، حيث قمنا باختيار عينة عشوائية بسيطة وتم توزيع الاستبيان عليهم جميعا من خلال عدة زيارات ميدانية وتم استرجاع 11 استبيان صالح للتحليل الاحصائي، وقد تم الاعتماد على عدة أساليب احصائية في تحليل البيانات منها مقاييس الاحصاء الوصفي، تحليل الانحراف المعياري ... حيث توصلت الدراسة الى عدة نتائج أبرزها وجود دور معنوي كبير لفيروس كورونا المستجد على طبقات المجتمع وأيضا تأثيره الكبير على مردودية ونشاط المؤسسات الصيدلانية، وخلصت الدراسة الى جملة من التوصيات أهمها: يجب على العاملين بالمؤسسات الصيدلانية أن يقدموا الدعم الكافي للمواطن من أجل التصدي للمرض و مواجهته والحرص على عدم انتقال العدوى بين الأفراد كما يعملون على تقديم النصائح و الارشادات اللازمة للوقاية وكيفية استعمال الأدوية.